556 Lost to Follow-Up: Post-Operative Polysomnography in High-Risk, Pediatric OSAs. (3rd May 2021) - Long, Benjamin; Arora, Subodh; McKinlay, Alex; Foster, Shannon; Hansen, Shana
Abstract: Introduction: Post-operative polysomnography (PSG) is recommended in certain pediatric populations at risk for residual sleep disordered breathing: moderate to severe obstructive sleep apnea syndrome (OSAS), obesity, craniofacial abnormalities, and neurologic disorders. In light of multiple stakeholders involved in follow-up management, variability in completion of a post-operative PSG may exist. We hypothesize that patients with isolated severe OSAS or severe plus a co-morbidity will have greater incidence of a post-operative PSG. Methods: A chart review of 373 pediatric patients revealed 67 patients who met inclusion criteria for our high-risk cohort. Chart review included the presence of an ENT, Primary Care, or Sleep Medicine encounter, time to follow-up, the presence of a post-operative PSG, time to post-operative PSG, and the presence of an annual follow-up with any provider. Results: Although 83% of our cohort followed-up with any provider, only 31% completed a post-operative PSG. Patients consistently followed-up with ENT 6–8 weeks postoperatively (76%) and haphazardly followed-up with primary care (38%). All patients with a Sleep Medicine follow-up (19%, n=13) completed a post-operative PSG, with 11 of the 13 occurring within 1 year from surgery. There was no significant difference across isolated moderate, isolated severe, or moderate/severe with a comorbidity for incidence of follow-up by specialty, annual follow-up, or post-operative PSG completion. However, patients with isolated severe (AHI >10) completed a PSG on average 13.5 weeks post-operatively which was significantly sooner than 36.2 weeks for isolated moderate OSA (p=0.04). Conclusion: Although Sleep Medicine providers may consistently follow AASM practice parameters, variability exists for which patients return to complete a post-operative PSG. Severity of OSAS or presence of a concerning co-morbidity does not seem to correlate with acquiring a postoperative PSG. An inconsistent standard across disciplines may contribute to this discrepancy. These findings will inform future quality improvement discussions with key stakeholders. In light of this baseline assessment, we plan to recommend a standardized, multi-disciplinary care pathway for the management of high-risk, pediatric OSAS. Support (if any): None